Efficacy of Targeted vs Standard Spermatic Cord Denervation in the Management of Chronic Orchialgia: A Comparative Study - Naqib Ullah, Muhammad Izhar, Zakir Khan, Navid Khan, Fahim Ullah, Sajid Shakeel (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To evaluate and compare the outcomes of targeted versus complete spermatic cord denervation in patients suffering from chronic orchialgia. Methods: A total of 50 patients presenting to Health Net Teaching Hospital, Hayatabad Peshawar with chronic testicular or scrotal pain (>3 months duration) were enrolled. Diagnosis was confirmed through clinical evaluation and diagnostic nerve block using local anesthetic and corticosteroid. Twenty-five patients underwent targeted denervation, while the remaining 25 underwent complete spermatic cord denervation. Results: In the standard denervation group, 19 patients (76%) reported complete resolution of pain, 2 (8%) reported partial relief, and 4 (16%) experienced no improvement. The targeted denervation group demonstrated complete resolution of pain 18 patients, and 6 patients has no improvement while one patient has partial pain, indicating no significant difference in outcomes between the two approaches. Conclusion: Both targeted and complete denervation are effective strategies for management of chronic orchialgia. Denervation should be considered a viable treatment option for patients with persistent orchialgia unresponsive to medical therapies and nerve block. Keywords: Targeted Spermatic Cord Denervation, Standard Spermatic Cord Denervation, Chronic Orchialgia